Gender and Climate Services Resources - Nsengiyumva, Gloriose; Rose, Alison (Accelerating Impacts of CGIAR Climate Research for Africa, 2022)
Women and men farmers can be differentially vulnerable to climate related risk due in part to the varied roles and responsibilities that they carry out in their communities and households. While climate services can be critical for enhancing farmers’ adaptive capacities, women and men can face varying opportunities and challenges to access climate services and implement climate information in agricultural decision-making.